1986
DOI: 10.1080/07315724.1986.10720145
|View full text |Cite
|
Sign up to set email alerts
|

A crossover trial of high and low sucrose-carbohydrate diets in type II diabetics with hypertriglyceridemia.

Abstract: Earlier work shows that hyperlipemic type II diabetics tolerate wide ranges of sucrose and carbohydrate intake without effects on glycemic control, but a rise of fasting serum triglycerides sometimes occurs. To address further the issue of individual susceptibility to carbohydrate, the current study was designed to use each patient as his own control when given diets widely varying in sucrose content. After a stabilization period in the hospital on a normal sucrose content diet, each subject was given either a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…However, current scientific literature suggests that consuming a moderate amount of dietary sucrosewithin a balanced meal-has an effect similar to starch on the glycemic level of patients with type 1 or type 2 diabetes (1). These studies were conducted in controlled environments where as much as 38% of calories were given as sucrose either alone or in mixed meals (2)(3)(4)(5)(6)(7)(8). In contrast, Coulston et al (5,6) found that diets containing 10 and 16% of total energy as sucrose resulted in a rise in fasting plasma glucose (FPG), total cholesterol (TC), triglycerides (TGs), and a reduction in HDL cholesterol.…”
mentioning
confidence: 99%
“…However, current scientific literature suggests that consuming a moderate amount of dietary sucrosewithin a balanced meal-has an effect similar to starch on the glycemic level of patients with type 1 or type 2 diabetes (1). These studies were conducted in controlled environments where as much as 38% of calories were given as sucrose either alone or in mixed meals (2)(3)(4)(5)(6)(7)(8). In contrast, Coulston et al (5,6) found that diets containing 10 and 16% of total energy as sucrose resulted in a rise in fasting plasma glucose (FPG), total cholesterol (TC), triglycerides (TGs), and a reduction in HDL cholesterol.…”
mentioning
confidence: 99%
“…In contrast with these studies, there are five reports that suggest that increased dietary sucrose consumption over a period of 8 days to 6 wk did not result in adverse metabolic effects (21)(22)(23)(24)(25). In one of these studies the authors reported no significant metabolic effects of replacing 45 g of complex carbohydrate with an equal amount of sucrose (21).…”
Section: Cb Hollenbeck Am Coulston and Gm Reaven Clinical Stumentioning
confidence: 58%
“…Unfortunately, the effects of this difference in baseline values on the glycemic response is difficult to evaluate. More important, fasting hypertriglyceridemia was noted in both of these studies after the high-sucrose diet (23,24). Thus, there appears to be only a single well-controlled metabolic study on patients with diabetes conducted over an 8-day period in which the authors reported no significant differences in metabolic control as a result of increased dietary sucrose (25).…”
Section: Effects Of Sucrose On Carbohydrate and Lipid Metabolismmentioning
confidence: 93%
See 2 more Smart Citations